46 Novel creep area heat source impact on pre-wean mortality occurrence. (30th November 2020) - Smith, Benjamin; Ramirez, Brett; Greiner, Laura L
Abstract: Pre-wean mortality (PWM) is a multifaceted problem facing the US swine industry. The objective of this study was to compare the occurrence of mortality and age of piglets between a novel heat source (HS; semi-enclosed heated microclimate; SEHM) and a conventional heat lamp setup. This study was conducted in two rooms at a 1, 000 head commercial sow farm. Treatments were blocked by sow parity group (SPG; young, prime, and geriatric) over six farrowing cycles. Litters were cross fostered within HS treatment at 1 day of age. PWM, was the experimental unit, data were collected from the farm's farrowing records and production accounting system. Age of the mortalities was categorized into four phases of lactation (PL) over the 20 d lactation (d0 to d3, d4 to d7, d8 to d11, and d12 to d20). Overall, there were 220 recorded instances of mortality. Data were analyzed in a CRBD using a PROC MIXED model in SAS (v9.4, SAS Inst., Cary, NC) and reported as LSMEANS with standard errors. The model included farrowing cycle as a random effect and the following fixed effects: HS, SPG, PL, HS*SPG, and HS*PL. Overall average PWM was 8.60%±0.80 for SEHM and 10.0%±0.70 for the heat lamps. There was no effect (P >0.05) of HS or HS*PL on PWM occurrence. There were significant effects of SPG (P=0.026), PL (P=0.05), and HS*SPG (P=0.036) on PWM occurrence. These data suggest that the HS type did not have an impact on the mortality rate or the timing of the mortality, indicating the mortalities that occurred had no relationship to HS. A limitation of this data set is the low sample size, thereby limiting the detection ability for this interaction. Further research into the impact of the HS is needed to expand the data set and to explore other popular HS effects on PWM.